"The Letter after Your Name": Party Labels on Virginia Ballots. (June 2015) - Garlick, Alex
Abstract: In 2000, Virginia became the last state in the nation to add party labels to its ballots for state-level races. This article assesses the impact of this reform on citizen participation and the partisan behavior of down-ballot voters using precinct-level election returns. It finds that after the application of labels, roll-off in contested, down-ballot races dropped by about a percentage point, a reduction of approximately 15%. Roll-off dropped more in precincts with a larger share of African Americans. Also, the association between Republican vote shares in the Lt. Governor and state legislative races and presidential vote share in the 2000 general election became stronger in the presence of party labels. This result suggests that the labels made voters behave more as national partisans in state-level contests.